Revision and Psychometric Testing of the Delirium Care Self-Efficacy Scale for ICU Nurses - Nie J; Jiang ZY (Journal of Multidisciplinary Healthcare)
Jing Nie, Zheng-Ying Jiang Intensive Care Unit, Chongqing University Cancer Hospital, Chongqing, 400030, People’s Republic of ChinaCorrespondence: Zheng-Ying Jiang, Intensive Care Unit, Chongqing University Cancer Hospital, No. 181 of Hanyu Road, Shapingba District, Chongqing, 400030, People’s Republic of China, Tel +86 13996489813, Email jiangzhengyingggg@126.comObjective: The aim of this study is to culturally adapt the Traditional Chinese version of the Delirium Care Self-Efficacy Scale for ICU Nurses (DCSE-I), originally developed in Taiwan, for use in mainland China and to assess its reliability and validity.Methods: The revised scale underwent cross-cultural adaptation following expert consultations and a pilot survey. To evaluate its reliability and validity, a survey was conducted among 284 ICU nurses from eight tertiary hospitals in Chongqing.Results: The Chinese version of the DCSE-I demonstrated strong internal consistency, with an overall Cronbach’s α coefficient of 0.934. The item-level content validity index (I-CVI) values ranged from 0.800 to 1.000, and the scale-level content validity index/average (S-CVI/Ave) was 0.923. The split-half reliability was 0.861, while the test-retest reliability reached 0.954. Exploratory factor analysis identified two factors with a cumulative variance contribution rate of 65.522%. These two dimensions were labeled “Confidence in Delirium Assessment” and “Confidence in Delirium Management”.Conclusion: The Chinese version of the DCSE-I is appropriate for the cultural context of mainland China and exhibits strong reliability and validity.Keywords: cultural adaptation, delirium care self-efficacy, ICU nurses, reliability, validity